The myth of sublime (sublimation) and the existence of Polish soldiers in the years 1806–1807 - Srogosz, Tadeusz (Marginesy, 2021)
The fundamental myth of sublimation is an important element of the Napoleonic legend. In sublimity we see general contours, devoid of everyday life. At work, the myth of sublimation was confronted with the difficult existence of Polish soldiers in 1807. History is an idiographic science, showing the whole wealth attitudes actions, facts, processes, interpretations, which is why I not intend to depreciate the heroic military history in the Napoleonic period and the myth of sublimation.